Data analysis - Sarantakos, S (Sotirios) (Sage benchmarks in social research methods., 2007)
'What is data analysis' is a key question in social research, defined by the foundations of various research models. This four-volume set presents the leading directions in data analysis and published in the 'classic' articles in the field. It brings together the most outstanding 'vintage' and contemporary work that have helped define and demarcate data analysis. It covers both quantitative and qualitative aspects, as centred around realism, positivism and empiricism on the one hand, and relativism and interpretivism on the other. Volume One: covers qualitative data analysis: choosing and processing data, approaches to analysis and analytic techniques. Volume Two: focuses on mixed methods: mixed method approaches and techniques, and the integration of findings. Volume Three: moves to quantitative data analysis: analysing survey data, text, structure and sequences, testing and multivariate analysis. Volume Four: concludes with issues surrounding the quality of research outcomes.